Perbuatan Melawan Hukum Oleh Penguasa (Onrechtmatige Overheids Daad) - Amrizal J. Prang (Jurnal Transformasi Administrasi, 2013)
Unlawful acts by authorities (onrechtmatige overheids daad) and Unlawful acts (onrechtmatige daad) governed by the same legal basis, namely Article 1365 Kitab Undang-Undang Hukum Perdata (Burgerlijk Wetboek), but has connotations and different settings. For tort claim made to the general court (civil). Meanwhile, the unlawful act by the authorities, sued the state administrative court, if the actions of individual governments, concrete, and final such, dismissal of civil servants, as stipulated in Act Number 5/1986 joncto Act Number 9/2004, joncto Act Number 51/2009. Meanwhile, general and abstract, like, Regent issued a decree in the implementation of a regional regulatory requirements. Furthermore, the general nature and concrete, such as the Regent issued a decree stating that Dengue Fever infected area and individual and abstract, such as permission to establish a factory paint with a variety of terms or conditions, it was possible to be sued to court general.